2014
DOI: 10.14214/sf.1161
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the Risutec Automatic Plant Container (APC) and Bracke planting devices

Abstract: Comparative study of the Risutec Automatic Plant Container (APC) and Bracke planting devicesLaine T., Saarinen V.-M. (2014). Comparative study of the Risutec Automatic Plant Container (APC) and Bracke planting devices. Silva Fennica vol. 48 no. 3 article id 1161. 16 p. Highlights• As currently designed, the prototype Risutec APC fitted with an automatic feeding system offers no significant advantage over the Bracke planting device in terms of planting productivity or quality.• Cost estimates suggest that an id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…Today's excavator-based planting machines generally cost less than 100 Euro h -1 (cf. Ersson et al 2014;Laine and Saarinen 2014;Guerra et al 2019), although the highly productive, forwarder-based Silva Nova planting machine of the 1990s had a much higher hourly cost than that (Hallonborg et al 1995). Machine-specific seedling packaging can't be dismissed entirely though, because it's likely that future tree planting machines' hourly cost will become equally expensive (because of continuous advancement like today's Plantmax prototype, or productivity enhancing innovations like e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Today's excavator-based planting machines generally cost less than 100 Euro h -1 (cf. Ersson et al 2014;Laine and Saarinen 2014;Guerra et al 2019), although the highly productive, forwarder-based Silva Nova planting machine of the 1990s had a much higher hourly cost than that (Hallonborg et al 1995). Machine-specific seedling packaging can't be dismissed entirely though, because it's likely that future tree planting machines' hourly cost will become equally expensive (because of continuous advancement like today's Plantmax prototype, or productivity enhancing innovations like e.g.…”
Section: Resultsmentioning
confidence: 99%
“…This seedling supply concept showed promise; however, it also showed to be too expensive for today's planting machines (Ersson 2014). Ersson et al (2014) and Laine and Saarinen (2014) studied seedling feeding systems for crane-mounted planting devices (Bracke Planter and Risutec) that did not require machine-specific seedling packaging. These innovative feeding systems (seedling carousels), however, suffered from low mechanical availability and were subsequently cost-inefficient.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming a full planting operation, the numbers presented above probably would have reached more than half a minute per planted tree, a fact that still remains open to research. Studies on manual planting, on the other hand, have shown results in the range of 6 [6] to 19-26 [5] seconds spent to plant a tree, while for mechanized planting one could expect values in the range of 15-18 s per tree [4]. However, the performance of both manual and mechanized planting operations depends largely on the operational conditions, tools, and technology used.…”
Section: Discussionmentioning
confidence: 99%
“…An onboard storage of 1500 seedlings was seen as reasonable to fit on the available terrain vehicle platform, but a single Hiko-tray was used for the integration tests (Figure 7). Automatic seedling transfer from the storage to the planting device is important for increasing the productivity of mechanized planting [34,35] but is challenging due to the sensitivity of the seedlings.…”
Section: Automatic Seedling Transfermentioning
confidence: 99%